1996
DOI: 10.1515/znb-1996-0916
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfonylamine, LXXVI [1] Zwei supramolekulare Isomere im gleichen Kristall: Darstellung und Struktur des monomeren 18-Krone-6-Komplexes (CH2CH2O)6·2 MeN(SO2Me)(SO2Ph) / Polysulfonylamines, LXXVI [1] Occurrence of Two Supramolecular Isomers in One Crystal: Synthesis and Structure of the Monomeric 18-Crown-6 Complex (CH2CH2O)6 • 2 MeN(SO2Me) (SO2Ph)

Abstract: The title complex, obtained by co-crystallization of its molecular components from methanol, was characterized by low-temperature X-ray diffraction. The crystal structure (triclinic, space group P1̄, Z = 2) consists of two monomeric and crystallographically centrosymmetric formula units A and B which may be classified as supramolecular stereo- and/or linkage isomers. In both units, the receptor rings adopt the frequently observed D3d pseudosymmetry, and the symmetry-related substrate molecules are situated abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
6
6
0
Order By: Relevance
“…In the title compound ( Fig. 1), all bond lengths and angles are normal (Allen et al, 1987) and in good agreement with those reported previously for similar molecules (Henschel et al, 1996). The molecular structure is stabilized by intramolecular C-H•••O hydrogen bonds involving the oxygen atoms bound to atom S1 (Table 1).…”
Section: Data Collectionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the title compound ( Fig. 1), all bond lengths and angles are normal (Allen et al, 1987) and in good agreement with those reported previously for similar molecules (Henschel et al, 1996). The molecular structure is stabilized by intramolecular C-H•••O hydrogen bonds involving the oxygen atoms bound to atom S1 (Table 1).…”
Section: Data Collectionsupporting
confidence: 88%
“…For literature on the biological activities of sulfonimide compounds, see: Kamoshita et al (1987). For the crystal structure of related compounds, see: Henschel et al (1996). For related literature, see: Allen et al (1987); Zhang et al (2007).…”
Section: Related Literaturementioning
confidence: 99%
“…For a related crystal structure, see: Henschel et al (1996). For applications of sulfonimide derivatives, see: Kamoshita et al (1987) and Zhang et al (2007).…”
Section: Related Literaturementioning
confidence: 99%
“…In addition, the nature and position of substituents play a significant role on the crystal structures of N-(aryl)-amides and N-(aryl)-sulfonamides (Gowda et al, 2007(Gowda et al, , 2010Shakuntala et al, 2011a,b;Henschel et al, 1996). In view of the importance of the biological activities of sulfonamide containing compounds, we report herein the crystal structure of the title compound.…”
Section: S1 Commentmentioning
confidence: 95%
“…For related structures, see : Henschel et al (1996); Gowda et al (2007Gowda et al ( , 2010 ;Shakuntala et al (2011a,b). For the stability of the temperature controller used in the data collection, see : Cosier & Glazer (1986).…”
Section: Related Literaturementioning
confidence: 99%